Pengaruh Lingkungan Keluarga terhadap Perkembangan Anak Usia Dini di Bidang Literasi: The Influence of Family Environment on Early Childhood Development in Literacy - Mukhlis, Mukhlis (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2023)
The family environment is considered an important factor in the development of early childhood literacy. Parents, as the main family members, have an important role in instilling literacy in children from an early age. The aim of this research is to determine the influence of the family environment, especially the role of parents on the development of early childhood literacy. This research method uses a qualitative approach, namely literature study by collecting data from related articles over the last ten years. Accumulate and analyze the data sourced from books, magazines, newspapers and other scientific works. Based on the research results, it was found that early childhood education has an important role in lifelong development, and the family environment, especially the role of parents, that a key factor in children's literacy development. The factors in the family environment that influence children's literacy development includes interactions between parents and children, the practice to reading together, a physical environment that supports literacy, and an emotional atmosphere at home. The suggestion of this research is that parents instill literacy in children from an early age through various literacy activities, build a supportive literacy environment, and involve children in creative literacy activities.